Method for analyzing consequences. - Mustapha, Saari; El-Harbawi, Mohanad (2009)

(untitled)
A method for providing a simulator for analyzing a plurality of consequences of accidents, comprising: assessing the plurality of consequences of accidents from at least one industry for simulating a set of hazardous events; and creating at least one map for visualizing a process decision making to locate the set of hazardous events.